Karakteristik Ekstrak Pewarna Alami Bunga Bugenvil (Bougainvillea glabra) Dengan Variasi Waktu Dan Daya Menggunakan Metode Microwave Assisted Extraction (MAE) - Suwariani, Ni Putu; Wartini, Ni Made; Aprilianti, Bunga (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Bougainvillea (Bougainvillea glabra) is a natural source of betacyine pigment which has the potential to be a food coloring as well as an antioxidant. This study aims to examine the effect of extraction time and power using the Microwave Assisted Extraction (MAE) method on the characteristics of bougainvillea flower extract, including yield, total betayanin, color intensity ( a*, b*), and antioxidant capacity. The study used a factorial Group Random Design (RAK) with two factors: time (3, 5, 7 minutes) and power (100, 300 watts). The results showed that the combination of time and power had a very pronounced effect (P<0.01) on all parameters. The best treatment was obtained at 5 minutes and a power of 100 watts, with a yield of 56.26±0,98%, total betasianine 20.56±0,24 mg/100g, color intensity a* 30.31±0,11; b* 16.06 ± 0,17, and antioxidant capacity of 495.27± 2,69 mg GAE/100g. The MAE method has been proven to be effective in producing high-quality bougainvillea flower extract as a natural dye and antioxidant.